Development and validation of a questionnaire to identify barriers to the implementation of the Clinical Practice Guidelines for lower limb amputees in a middle-income country Colombia (2024)
ABSTRACT: Aim: To develop and validate a questionnaire to identify the perceivedbarriers in the implementation of the Clinical Practice Guidelines for thelower limb amputee (CPG‐AMP).Study Design and Setting: The study consisted of two stages: ﬁrst, thedevelopment of the questionnaire based on a meta‐review of the literatureand interviews with patients and health providers (mixed‐methodsresearch). Second, the evaluation of its psychometric properties wasperformed. Participants included health providers from hospitals and clinics,prosthetic workshops and academic institutions in Colombia.Results: A total of 90 items were obtained from the literature review andinterviews. The validation of a preliminary 66‐item questionnaire wasperformed with 545 participants. After the factorial analysis, a 25‐itemquestionnaire with four domains was developed. Internal consistency wasadequate in all domains, with Cronbach's α values between 0.76 and 0.83.Test–retest reliability in 58 participants yielded intraclass correlationcoefﬁcients between 0.51 and 0.59.Conclusions: A 25‐item questionnaire with four domains (health system,guideline, institutional and individual) was proposed to measure theperception of barriers to the CPG‐AMP. The conceptual framework andthe questionnaire can be used to identify barriers of other CPGs and to help design strategies aimed at improving its implementatio.